The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1021/jacsau.2c00014
|View full text |Cite
|
Sign up to set email alerts
|

DFT Mechanistic Insights into Aldehyde Deformylations with Biomimetic Metal–Dioxygen Complexes: Distinct Mechanisms and Reaction Rules

Abstract: Aldehyde deformylations occurring in organisms are catalyzed by metalloenzymes through metal–dioxygen active cores, attracting great interest to study small-molecule metal–dioxygen complexes for understanding relevant biological processes and developing biomimetic catalysts for aerobic transformations. As the known deformylation mechanisms, including nucleophilic attack, aldehyde α-H-atom abstraction, and aldehyde hydrogen atom abstraction, undergo outer-sphere pathways, we herein report a distinct inner-spher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
(194 reference statements)
0
8
0
Order By: Relevance
“…Quantum mechanical density functional theory (DFT) methods have found a wide range of applications, especially in the field of predicting the properties of nanomaterials 24 27 , separation and purification of chemicals 28 30 , prediction of the mechanism of reactions 31 , and so on. Recently, some important methods such as functionalization/doping and size-dependent were used to enhance or control the material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Quantum mechanical density functional theory (DFT) methods have found a wide range of applications, especially in the field of predicting the properties of nanomaterials 24 27 , separation and purification of chemicals 28 30 , prediction of the mechanism of reactions 31 , and so on. Recently, some important methods such as functionalization/doping and size-dependent were used to enhance or control the material properties.…”
Section: Introductionmentioning
confidence: 99%
“…Although the further hydrogen abstraction of the Cu­(II)–O • complex is expected to generate a Cu­(II)-OH complex, the energy barriers of the above pathways for the generation of the Cu­(II)-O • complex have already exceeded 33 kcal/mol, showing that this mechanism is less possible. Cheng et al reported the addition of Cu­(II)-O-O • species to the formyl group of aldehydes, followed by 1,2-alkyl shift and hydrogen atom abstraction to produce Cu­(II)–OH . However, at the beginning of the aminooxygenation reactions, there is no aldehyde for realizing such a pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Cheng et al reported the addition of Cu(II)-O-O • species to the formyl group of aldehydes, followed by 1,2-alkyl shift and hydrogen atom abstraction to produce Cu(II)−OH. 23 However, at the beginning of the aminooxygenation reactions, there is no aldehyde for realizing such a pathway.…”
Section: In Situ Generation Of Active Cu(ii) Complexes From Lcuoacmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal–dioxygen species such as metal–(hydro)­peroxo [M–O 2 (H)] complexes have been invoked as important reactive intermediates for various oxidative reactions in biological systems. For examples, numerous M–O 2 (H) complexes have been reported to conduct nucleophilic reactions, including aldehyde deformylation in biomimetic models. Several M–O 2 (H) species have been documented to readily oxidize nitriles under mild conditions (Scheme ). In a rhodium complex with tert -butyl isocyanide and triethylphosphine ligands, it was revealed that the rhodium­(III)–hydroperoxo intermediate is responsible for the nitrile activation to afford a rhodium­(III)–peroxyimidato species (step a) .…”
Section: Introductionmentioning
confidence: 99%